Risk of death with sodium-glucose co-transporter-2 inhibitors across the hallmark cardiovascular and renal outcome trials: an updated meta-analysis. (14th October 2021) - Patoulias, D; Boulmpou, A; Tranidou, A; Nikolaidis, A; Mouselimis, D; Papadopoulos, C E; Vassilikos, V; Doumas, M
Abstract: Background: Patients with type 2 diabetes mellitus (T2DM) experience a 15% increase in the risk for death compared to the general population, with age less than 55 years, insufficient glycemic control and albuminuria representing the major risk factors for all-cause and cardiovascular mortality. Despite progression in diagnosis and treatment, mortality remains elevated among affected individuals. Sodium-glucose co-transporter 2 (SGLT-2) inhibitors are considered as the optimal treatment option for patients with T2DM and concomitant cardiovascular or renal disease, while these regimens demonstrated a clear benefit in all-cause and cardiovascular mortality compared to placebo. Purpose: As we recently welcomed the publication of large-scale randomized controlled trials (RCTs) with SGLT-2 inhibitors addressing surrogate, hard endpoints, we sought to perform an updated meta-analysis, investigating the effect of SGLT-2 inhibitors on all-cause, cardiovascular and renal death among the high- or very-high risk patients enrolled in those trials. Methods: We pooled data from the relevant, recent hallmark RCTs; 10 trials were included in our analysis encompassing a total of 71, 533 enrolled participants, assigned either to SGLT-2 inhibitor treatment or placebo. We set cardiovascular death as the primary efficacy outcome, while we assessed all-cause death and renal death as secondary efficacy outcomes. Results: Treatment with SGLT-2 inhibitors resulted in a significant decrease in the risk of cardiovascular death, equal to 14% (RR = 0.86, 95% CI; 0.80 to 0.93, I 2 =22%). Only canagliflozin produced a significant result, while dapagliflozin led to a marginally non-significant reduction in cardiovascular mortality (Figure 1). Notably, SGLT-2 inhibitors led to a significant decrease in the risk for all-cause death, equal to 14% (RR=0.86, 95% CI; 0.81 to 0.92, I 2 =34%) the result was significant only for canagliflozin and dapagliflozin, while none of the rest SGLT-2 inhibitors resulted in a significant decrease in the risk for all-cause death (Figure 1). SGLT-2 inhibitors also produced a non-significant decrease in the risk for renal death (RR=0.36, 95% CI; 0.12 to 1.14, I 2 =0%). Neither canagliflozin nor dapagliflozin had a significant impact on risk reduction for renal death, while no cases of renal death were reported in VERTIS CV trial. No subgroup differences were identified for any of the three comparisons (Figure 2). Conclusions: Antidiabetic treatment with SGLT-2 inhibitors provides a clear benefit in terms of cardiovascular and all-cause mortality for the very high-risk patients enrolled in the cardiovascular and renal outcome trials. Canagliflozin seems to be associated with the greatest impact on risk reduction for all-cause and cardiovascular death, followed by dapagliflozin. Funding Acknowledgement: Type of funding sources: None.